DAMPAK KEBIJAKAN MONETER TERHADAP PROFITABILITAS PERBANKAN KONVENSIONAL DI INDONESIA SEBELUM DAN SETELAH COVID-19 - admin, jekt; Paramita, Ni Komang Wahyudiyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 10 (2024): Vol.13.No.10. OKTOBER 2024 [686-751], 2025)
This research was conducted to analyze the impact of monetary policy on the profitability of conventional banking in Indonesia before and after the Covid-19 pandemic. The population in this research is conventional banking in Indonesia which is included in Bank BUKU 4. Samples were taken using the saturated sampling method or total sampling where the entire population was used as a sample. Conventional banking profitability is measured using ROA using techniques using the Eviews program. Hypothesis testing is carried out using panel data regression analysis. The results of this research show that inflation, Reserve Requirements Ratio (RRR), and exchange rates have a partial effect on the profitability of conventional banking in Indonesia. BI-7 Days Reverse Repo Rate and the Covid-19 Pandemic have no partial effect on conventional banking profitability. Meanwhile, the BI-7 Days Reverse Repo Rate, Reserve Requirements Ratio (RRR), Inflation, Exchange Rate and the Covid-19 Pandemic Dummy simultaneously influence the profitability of Conventional Banking in Indonesia.     keyword : BI-7 Days Reverse Repo Rate, reserve requirements ratio, Inflation, Exchange Rates, Covid-19 Pandemic, Profitability